Effect of Post Construction Alloy Type (NPG and Ni-Cr) and Cement Type on Fracture Resistance of Endodontically Treated and Restored Teeth by Cast Post-Core - Hadi, Alireza; Sheikh, Mohamad Amin (Journal of Dental School, 2023)
Objectives It is claimed that non-precious gold (NPG) alloys with modulus of elasticity (MOE) very close to dentin’s MOE can enhance the fracture resistance of endodontically treated teeth. Since limited studies have been conducted on these alloys, in this study, we tried to investigate the effect of cast alloys with MOE close to dentin and also the use of resin and zinc phosphate cement on the fracture resistance of endodontically treated teeth. Methods Forty mandibular single canal premolar teeth were assessed after post space endodontic treatment and preparation. The samples were randomly divided into four groups: Group A: Ni-Cr alloy + zinc phosphate cement, group B: Ni-Cr alloy + resin cement (Panavia® F2), group C: NPG alloy + zinc phosphate cement, and group D: NPG alloy + resin cement (Panavia® F2). The force needed for fracture and the fracture pattern of each tooth were recorded. The Shapiro-Wilk test was used to examine the normality of data distribution, Levene’s test was used to examine the equality of variances, and Fisher’s test was used to examine the equality of qualitative variables in the groups. Results A statistically significant difference was observed between the two post-core construction alloys (P<0.0001) and also between the two types of cement used (P<0.001). However, the interaction between alloy and cement type was insignificant (P=0.144). NPG alloy and Panavia® F2 cement showed better results than the other groups. Conclusion The NPG alloy + Panavia® F2 cement technique is preferred in reconstructing endodontically treated teeth.